2017
DOI: 10.5423/ppj.oa.10.2016.0214
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pyrenophora tritici-repentis (Tan Spot of Wheat) Races in Baltic States and Romania

Abstract: Tan spot, caused by the fungus Pyrenophora triticirepentis, is economically important foliar disease in Latvia, Lithuania, and Romania; however, race structure from Baltic States and Romania is not known. In this study, we performed genotypic and phenotypic race characterization of a large collection of P. triticirepentis isolates from these countries to determine race structure and utilize this information for better disease management and breeding wheat for tan spot resistance. We characterized 231 single sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
2
19
1
Order By: Relevance
“…The isolates without Ptr ToxA and PtrToxB genes were observed in all three years 2012, (19 isolates, 13.8%), 2013 (9 isolates, 5.1%) and in 2014 (29 isolates, 11.7%) but they varied in their proportion (Figure 2). Our results indicate that majority (n=502) of the isolates collected over the three-year period from South Dakota carry Ptr ToxA gene that validate reports indicating prevalence of Ptr ToxA carrying isolates in abundance in South Dakota [12,31,32]. Availability of P. tritici-repentis whole genome information [33] may help in accelerating the development of molecular markers for race 3 and 4 and minimize the dependency on phenotyping which is a timeconsuming procedure and requires a well-trained person for observing the isolates phenotypic reaction.…”
Section: Genotypic Characterization Of P Tritici-repentis Isolates Fsupporting
confidence: 72%
See 2 more Smart Citations
“…The isolates without Ptr ToxA and PtrToxB genes were observed in all three years 2012, (19 isolates, 13.8%), 2013 (9 isolates, 5.1%) and in 2014 (29 isolates, 11.7%) but they varied in their proportion (Figure 2). Our results indicate that majority (n=502) of the isolates collected over the three-year period from South Dakota carry Ptr ToxA gene that validate reports indicating prevalence of Ptr ToxA carrying isolates in abundance in South Dakota [12,31,32]. Availability of P. tritici-repentis whole genome information [33] may help in accelerating the development of molecular markers for race 3 and 4 and minimize the dependency on phenotyping which is a timeconsuming procedure and requires a well-trained person for observing the isolates phenotypic reaction.…”
Section: Genotypic Characterization Of P Tritici-repentis Isolates Fsupporting
confidence: 72%
“…These isolates produced necrosis (Figure 4) like race 2, however, lacked Ptr ToxA so were categorized as unknown races. Recovery of these types of P. tritici-repentis isolates is not surprising as they have been noted in other independent studies as well [9,15,26,31]. Further, the occurrence of necrosis producing isolates without Ptr ToxA gene on the Ptr ToxA sensitive wheat genotype indicates presence of additional toxin(s) responsible for necrosis symptoms.…”
Section: Phenotypic Evaluation Of P Tritici-repentis Isolates For Ramentioning
confidence: 58%
See 1 more Smart Citation
“…Surveys of Ptr isolates from several countries have shown that presence or absence of the ToxB gene varies by region. For example, ToxB has been shown to be absent in Ptr from Australia (from a screen of 119 isolates; Antoni et al 2010), New Zealand (12 isolates; Weith 2015) and Latvia, Lithuania and Romania (223 isolates; Abdullah et al 2017), but present in Canada (Lamari et al 2005a), Algeria (Benslimane 2018;Lamari et al 1995;, Azerbaijan, Turkey , Syria, Turkey 2005b) and the USA (Abdullah 2017;Ali et al 1999). Given that modern wheat breeding programmes often incorporate germplasm from around the world, knowledge of varietal differences in ToxB sensitivity will inform wheat breeding in regions where Ptr isolates carry the ToxB gene, or in regions predicted to be prone to incursions of ToxB carrying Ptr isolates.…”
Section: Sensitivity Of North-western European Wheat To Toxbmentioning
confidence: 99%
“…Though initially described as an occasional wheat pathogen, the incidence of tan disease has increased markedly in recent times, and the pathogen exhibits a wide geographic range. Countries affected include those in North America (Canada, the USA and Mexico) (Ali and Francl, 2003;Singh and Hughes, 2006;Lamari et al, 1998;Friesen et al, 2005); South America (Colombia, Ecuador, Peru, Brazil, Uruguay and Argentina) (Gurung et al, 2013;Dubin, 1983;Gamba et al, 2012;dos Santos et al, 2002;Moreno et al, 2008); North Africa (Morocco, Algeria and Tunisia) (Lepoint et al, 2010;Cherif et al, 1994;Lamari et al, 1995); Europe (UK, Belgium, Luxembourg, Germany, Denmark, Czechia, Slovakia, Hungary, Poland, Romania, Bulgaria Lithuania, Latvia, Sweden and Finland) (Todorova, 2006;Sidrat et al, 2016;Abdullah et al, 2017;Gurung et al, 2013;Hudcovicova et al, 2015;Sierotzki et al, 2007;Cook and Yarham, 1989;Jalli et al, 2011;Leisova et al, 2008;Lepoint et al, 2010); Asia (Turkey, Syria, Georgia, Armenia, Azerbaijan, Russia, Iran, Turkmenistan, Uzbekistan, Tajikistan, Kyrgyzstan, Kazakhstan, Pakistan, India, Nepal, Bangladesh and Japan) (Singh, 2007;Ali and Francl, 2001;Gurung et al, 2013;Aboukhaddour et al, 2011;Momeni et al, 2014;Lamari et al, 2003Lamari et al, , 2005Mironenko et al, 2016;Lepoint et al, 2010) and Australasia (Australia and New Zealand) (Murray and Brennan, 2009;Hampton and Matthews, 1978). Both bread wheat (Triticum aestivum) a...…”
Section: Introductionmentioning
confidence: 99%